Poly(lactic acid) : synthesis, structures, properties, processing, and applications - Auras, Rafael (Hoboken, N.J. : Wiley, 2010)
This book describes the synthesis, properties, and processing methods of poly(lactic acid) (PLA), an important family of degradable plastics. As the need for environmentally-friendly packaging materials increases, consumers and companies are in search for new materials that are largely produced from renewable resources, and are recyclable. To that end, an overall theme of the book is the biodegradability, recycling, and sustainability benefits of PLA. The chapters, from a base of international expert contributors, describe specific processing methods, spectroscopy techniques for PLA analysis.
pt. 1. Chemistry and production of lactic acid, lactide, and poly(lactic acid) -- pt. 2. Properties of poly(lactic acid) -- pt. 3. Processing and conversion of poly(latic acid) -- pt. 4. Degradation and environmental issues -- pt. 5. Applications.
Includes bibliographical references and index.
Print version record.
Keywords: Biodegradable plastics; Lactic acid; Polymers; Engineering; Chemical engineering; TECHNOLOGY & ENGINEERING -- Material Science; Biodegradable plastics; Lactic acid; Polymers; Electronic books; Electronic books